STRESS TESTS FOR VIDEOSTREAMING SERVICES BASED ON RTSP PROTOCOL - Gabriel Elías Chanchí Golondrino; Franco Arturo Urbano Ordoñez; Wilmar Yesid Campo Muñoz (Tecnura, 2015)
Video-streaming is a technology with major implications these days in such diverse contexts as education, health and the business sector; all of this regarding the ease it provides for remote access to live or recorded media content, allowing communication regardless of geographic location. One standard protocol that enables implementation of this technology is real time streaming protocol, or RTSP. However, since most application servers and Internet services are supported on HTTP requests, very little research has been done on generating tools for carrying out stress tests on streaming servers. This paper presents a stress measuring tool called Hermes, developed in Python, which allows calculation of response times for establishing RTSP connections to streaming servers, as well as obtaining RAM memory consumption and CPU usage rate data from these servers. Hermes was deployed in a video-streaming environment where stress testing was carried out on the LIVE555 server, using calls in the background to VLC and OpenRTSP open source clients.